2012
DOI: 10.1371/journal.pone.0051122
|View full text |Cite|
|
Sign up to set email alerts
|

High Potential for Using DNA from Ancient Herring Bones to Inform Modern Fisheries Management and Conservation

Abstract: Pacific herring (Clupea pallasi) are an abundant and important component of the coastal ecosystems for the west coast of North America. Current Canadian federal herring management assumes five regional herring populations in British Columbia with a high degree of exchange between units, and few distinct local populations within them. Indigenous traditional knowledge and historic sources, however, suggest that locally adapted, distinct regional herring populations may have been more prevalent in the past. Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 78 publications
7
51
0
Order By: Relevance
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…A r c h a e o g e n e t i c a n a l y s e s o f f i s h b o n e s Until now, fish remains have rarely been used for ancient DNA analyses, even though they can be found at archaeological sites in high numbers, and their potential in palaeoecological and palaeoeconomical questions has occasionally been demonstrated (Arndt et al 2003;Speller et al 2012;Shirak et al 2013; BALTICA 23 Hutchinson et al 2015). In the Baltic Sea region, during the last decade, it was sturgeon that came into the focus of genetic research.…”
Section: Baltica 23mentioning
confidence: 99%
“…The application of diversity indices, measures of trophic alteration, aDNA analysis, and stable isotope analysis not only track changes in fish community structure and range as represented in the archaeological record but contribute unique perspectives to modern fisheries research (e.g., Butler and Delacorte 2004;Pauly et al 1998;Van Neer and Ervynck 2009). A balance between marine research and social science datasets is required, but the emphasis on establishing multidisciplinary research projects (e.g., Sea Around Us Project and Oceans Past Platform; see also Barrett et al 2004a;Jackson et al 2001;Kittinger et al 2011;Miller et al 2011;Speller et al 2012) will continue to redirect this discourse and ideally provide holistic conservation and management outcomes (Christie 2011).…”
Section: Resource Sustainability and Fisheries Managementmentioning
confidence: 99%
“…Stable isotope, aDNA, and DNA analysis have become critical components of interdisciplinary historical ecology research and provide insight into changes in population structure, interaction, adaptation, population size estimates, trophic ecology, and alterations to prey, habitat, and foraging preferences of taxa over time-also including humans. Speller et al (2012) used aDNA to study genetic diversity and population structure of prehistoric herring populations, research key to understanding temporal and spatial genetic variations in fish populations (see PÀÀbo et al 2004;Willerslev and Cooper 2005). aDNA can be utilised to identify species introductions and translocations, particularly relevant to island archaeology (Rick et al 2014: 688) Leach et al 1998Leach et al , 2003.…”
Section: Fisheries Managementmentioning
confidence: 99%
See 1 more Smart Citation